THE ANALYSIS OF INTERCULTURAL COMMUNICATION IN BORAT'S MOVIE - Ni Komang Sri Mariati; Ni Luh Putu Sri Adnyani; Ni Nyoman Padmadewi (Elite : English and Literature Journal, 2022)
Intercultural communication is essential to help people learn a new culture and communicate their own culture to other groups/countries. Since many people have to misinterpret the new culture, intercultural communication is important to learn. The study aims to analyze the differences between Kazakhstan and American culture toward intercultural communication contained in Borat's movie. This study uses the library research method. The researcher collects the data from some books, articles, and journals. The findings of the research are; first, the researcher found that in the movie, there are surface and deep cultural differences between Kazakhstan and American culture. The surface culture found are people, buildings, dress, language, and behavior. Then, the deep cultures that are found are values and attitudes. Second, intercultural communication works when the main character and people in the USA share their culture. In the last findings, as the main character, Borat changes his mindset about Jews and shares Christian religion with Kazakhstan's people he adopts from the USA.